2023
DOI: 10.30574/ijsra.2023.8.1.0193
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of consumption patterns of soft drinks and its impact on nutritional status among young adults of Kolkata

Abstract: Soft drinks are non-alcoholic beverages that primarily consist of fruit juices and carbonated beverages. Soft drinks and other liquids with added sugar are viewed as unhealthy food items since they are high in calories but low in nutrients. India's populace continues to crave sugary soft drinks even as the rest of the globe is losing interest in these toxic beverages. The purpose of the present study was to determine the association between consumption of soft drinks and its impacts on nutritional status. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…From this perspective, several beverages, such as citrus‐based, carbonated and energy drinks, may have a pH (less than 5) favourable for tooth degradation 11 . Studies have shown that these beverages are widely consumed daily in Africa, Asia, Oceania, Europe and the Americas, especially among younger people 12–15 . They represent a large portion of beverages consumed by the general population, which grows yearly 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this perspective, several beverages, such as citrus‐based, carbonated and energy drinks, may have a pH (less than 5) favourable for tooth degradation 11 . Studies have shown that these beverages are widely consumed daily in Africa, Asia, Oceania, Europe and the Americas, especially among younger people 12–15 . They represent a large portion of beverages consumed by the general population, which grows yearly 16 …”
Section: Introductionmentioning
confidence: 99%
“…11 Studies have shown that these beverages are widely consumed daily in Africa, Asia, Oceania, Europe and the Americas, especially among younger people. [12][13][14][15] They represent a large portion of beverages consumed by the general population, which grows yearly. 16 Therefore, in addition to pH, titratable acidity, the concentration of calcium and phosphates, and temperature are the factors that most influence the erosive potential of beverages, which may have consequences for consumers' oral health.…”
mentioning
confidence: 99%